Sevoflurane postconditioning attenuates cardiomyocyte hypoxia/reoxygenation injury via restoring mitochondrial morphology - Jin Yu (PeerJ, 2016)
Background Anesthetic postconditioning is a cellular protective approach whereby exposure to a volatile anesthetic renders a tissue more resistant to subsequent ischemic/reperfusion event. Sevoflurane postconditioning (SPostC) has been shown to exert cardioprotection against ischemia/reperfusion injury, but the underlying mechanism is unclear. We hypothesized that SPostC protects cardiomyocytes against hypoxia/reoxygenation (H/R) injury by maintaining/restoring mitochondrial morphological integrity, a critical determinant of cell fate. Methods Primary cultures of neonatal rat cardiomyocytes (NCMs) were subjected to H/R injury (3 h of hypoxia followed by 3 h reoxygenation). Intervention with SPostC (2.4% sevoflurane) was administered for 15 min upon the onset of reoxygenation. Cell viability, Lactate dehydrogenase (LDH) level, cell death, mitochondrial morphology, mitochondrial membrane potential and mitochondrial permeability transition pore (mPTP) opening were assessed after intervention. Mitochondrial fusion and fission regulating proteins (Drp1, Fis1, Mfn1, Mfn2 and Opa1) were assessed by immunofluorescence staining and western blotting was performed to determine the level of protein expression. Results Cardiomyocyte H/R injury resulted in significant increases in LDH release and cell death that were concomitant with reduced cell viability and reduced mitochondrial interconnectivity (mean area/perimeter ratio) and mitochondrial elongation, and with reduced mitochondrial membrane potential and increased mPTP opening. All the above changes were significantly attenuated by SPostC. Furthermore, H/R resulted in significant reductions in mitochondrial fusion proteins Mfn1, Mfn2 and Opa1 and significant enhancement of fission proteins Drp1 and Fis1. SPostC significantly enhanced Mfn2 and Opa1 and reduced Drp1, without significant impact on Mfn1 and Fis1. Conclusions Sevoflurane postconditioning attenuates cardiomyocytes hypoxia/reoxygenation injury (HRI) by restoring mitochondrial fusion/fission balance and morphology.